A large creditor in contagious liquidity crises - Oh, Frederick Dongchuhl; Park, Junghum (Journal of Banking & Finance, 2023)
This paper presents a contagious liquidity crises model for nonfinancial firms in which a large creditor influences the extent to which the contagion spreads across firms. We consider a sequential framework where two rollover games occur one after another. A liquidity crisis in one firm triggers a liquidity crisis in another firm through changes in the risk attitudes of creditors from the wealth effect. We show that the presence of a large creditor with a sufficient asset size reduces the contagion effect. Moreover, a concentration of a large creditor’s loan portfolio towards the former firm increases the contagion effect. (JEL G01, G33, D82, D83).